Some physical and thermodynamic properties of n-cnf2n+2 compounds with n = 4-8 - Marcelo Campos-Vallette; Guillermo Diaz-Fleming (Semina: Ciências Agrárias, 1983)
Thermodynamic constants (Cv> Cp and itf) and physical properties a, fis and v) of the n-CnF2n+2 compounds with n=4 to 8 were evaluted and estimated from correlations. The values are compared with those obtained for the corresponding molecules in the n-CnH2n+2 series and tfje results were found to be consistent with the published experimental data. The liquid structure or n-perfluorated compounds is discussed on the basis of these data.